2018
DOI: 10.1017/s0033291718002775
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of working memory and processing speed training in schizophrenia

Abstract: BackgroundAlthough prior research has shown that cognitive training may improve cognition for schizophrenia patients, it is currently unclear which domains of cognition should be targeted in training. One suggestion is to target low- or mid-level cognitive processes. In particular, working memory (WM) and processing speed (PS) have been named as two key areas of impairment in schizophrenia, and two domains of cognition that are linked to higher-order cognition and daily functioning. This study aimed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
12
0
2
Order By: Relevance
“…Out of the 26 studies included, two included a paper-and-pencil format that had dropout rates of 0 [ 9 ] and 8 [ 15 ]. Twenty-three studies included a computerized CRT program with dropout rates ranging from 0 to 53 [ 7 , 8 , 10 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. One study compared paper-and-pencil and computerized CRT to one another and had 9 total dropouts [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 26 studies included, two included a paper-and-pencil format that had dropout rates of 0 [ 9 ] and 8 [ 15 ]. Twenty-three studies included a computerized CRT program with dropout rates ranging from 0 to 53 [ 7 , 8 , 10 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. One study compared paper-and-pencil and computerized CRT to one another and had 9 total dropouts [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both group and individual formats implementing CRT were found from our search. Of the 26 articles, nine studies used an individual format [ 7 , 11 , 12 , 13 , 14 , 23 , 24 , 29 , 31 ] and 17 used a group format [ 8 , 9 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 25 , 26 , 27 , 28 , 30 , 32 ]. One study [ 22 ] had participants complete homework exercises in their own homes, but the CRT program itself was implemented in a group outpatient setting.…”
Section: Resultsmentioning
confidence: 99%
“…Processing speed appears to be particularly important to measure in UHR individuals, also for screening purposes (González‐Blanch et al., 2011), because it may capture the generalized impairment. From a treatment perspective, our study may provide a rationale for targeting this apparently domain‐general neurocognitive mechanism, using behavioral and/or pharmacological interventions to boost neurocognitive processing efficiency (Brébion et al., 2014; Cassetta & Goghari, 2016; Cassetta et al., 2019; Takeuchi & Kawashima, 2012). Thus, a double‐blind randomized clinical trial has shown that UHR individuals receiving processing speed training exhibit improvement not only in processing speed but also in social functioning (Choi et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As there are currently no investigations in schizotypy or schizophrenia that compares performance to controls on the GERT-S, it cannot be ruled out that our findings are due to the ER instrument used. However, one study has assessed patients using the GERT-S (with no control group) and reported an average score of 53.5% ( 68 ). The average score in this control sample was 62.9% which may suggest the GERT-S is sensitive to detect ER deficits in psychosis patients.…”
Section: Discussionmentioning
confidence: 99%